2009
DOI: 10.1002/gps.2275
|View full text |Cite
|
Sign up to set email alerts
|

Non‐pharmacological management of behavioural symptoms in nursing homes

Abstract: The intervention reduced BPSD in severely demented nursing home residents and this effect was still present 3 months after the end of the programme.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
96
0
2

Year Published

2010
2010
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 91 publications
(98 citation statements)
references
References 20 publications
(22 reference statements)
0
96
0
2
Order By: Relevance
“…Only five of the studies (42%) reviewed, however, conducted follow-up assessments that ranged from six weeks to six months. [31,33,36,39,42] These findings represent a slight improvement from those of Buchanan et al, [29] who found that only 22% studies included any kind of follow-up assessment. Nevertheless, more studies must assess whether treatment gains maintain over time as the disease progresses and what sorts of modifications are necessary to accommodate this progression.…”
Section: Lack Of Follow-upmentioning
confidence: 53%
See 3 more Smart Citations
“…Only five of the studies (42%) reviewed, however, conducted follow-up assessments that ranged from six weeks to six months. [31,33,36,39,42] These findings represent a slight improvement from those of Buchanan et al, [29] who found that only 22% studies included any kind of follow-up assessment. Nevertheless, more studies must assess whether treatment gains maintain over time as the disease progresses and what sorts of modifications are necessary to accommodate this progression.…”
Section: Lack Of Follow-upmentioning
confidence: 53%
“…Deudon and colleagues [39] conducted a randomized controlled trial in 16 nursing homes with 306 individuals with dementia. An eight-week staff education and training program was completed in the nursing homes with the goal of reducing problem behaviors, including aggression.…”
Section: Staff Interventionsmentioning
confidence: 99%
See 2 more Smart Citations
“…For this goal we need to have training programs having demonstrated their efficacy and therefore we need to boost clinical research in this field. That was the aim of the TNM (Traitement Non Médicamenteux) which aimed to evaluate the effectiveness of a staff education intervention to manage behavioural disturbance in older people with a diagnosis of dementia (Deudon et al, 2009). After such demonstration and the present grant application of the Fédération de Coopération Scientifique, the major the major challenge of the French National plan for AD, is to promote the feasibility of applying the programme to all nursing homes in France.…”
mentioning
confidence: 99%